การประเมินศักยภาพและผลกระทบ จากการท่องเที่ยวต่ออุทยานแห่งชาติทางทะเล เพื่อการท่องเที่ยวเชิงนิเวศ รายงานส่วนที่ 1 : อุทยานแห่งชาติ ตะรุเตา จ.สตูล - อำพร วิริยโกศล (มหาวิทยาลัยสงขลานครินทร์, 2022)
The objectives of this study, "An Evaluation of Potential and Tourism Impact of Marine National Parks for Ecotourism Development", were to evaluate the tourism potentials and economic and social impacts, to evaluate the economic values in the Tarutao and Sirinath National Parks, to find the suitable form of ecotourism, and to find the guidelines for preventing social problems in order for the park development. This study was an explanatory research covering 4 sample groups, the tourists, the local people, the govemment officials, and the entrepreneurs. Data were collected from both the primary and secondary sources and analyzed through descriptive statistics. Principles and theories concerning ecotourism were used to analyze the social and economic potentials. Travel Cost Method (ICM) was used to analyze and evaluate the economic values of tourism. In the case of the Tarutao National Park, there were 4 groups of sample population covering altogether 624 persons, 104% of the planned samples. They consisted of 405 tourists of which were 293 Thai and 112 foreign tourists, 137 local pcople, 47 govemnment officials, and 35 entrepreneurs. The following results were found. Regarding the economic potentials, the Tarutuo National Park was found to gain high potential and have tourism activities which could be develop by following the principles of ecotourism. Four factors were considered :1) Natural tourism resources and activities which attract high satisfaction from Thai and foreign tourists. The local people, the entrepreneurs, and the goverment officials agreed that the Pak Bara Port, on the mainland coast, should be developed to increase the capacity for servicing larger number of tourists, 2) Concerning laws, rules and regulations, all four sample groups agreed that they must be effectively enforced, obeyed and assisted by all, 3) Regarding people participation in the economic aspects, it was accepted that the local cconomy was clearly improved through tourism, 4) Considering the joint- learing process, the tourists and the local people jointly learned about natural environment and historical places of interest. From the study of economic impacts, it was found that the Tarutao National Park had the tourism economic value of 78.2 million baht, which was highly significant to the economy of the local community. The average cost per trip for the foreign and Thai tourists was only 3}453.31 baht which was very low. The elasticity of travel cost to demand was also very low. Tourism generated high direct and indirect economic impacts on the conce med people. The travel cost could still be raised. From the survey, tourists were willing to pay more and assist the government officials to improve the facilites and develop the environment for better sustainability. Regarding the social potential, the Tarutao National Park had medium potential according to the following considerations: 1) Natural resources were unique and diversed which were positive factors, 2) Law, rule and regulation enforcement still found difficulties on some aspects, 3) Participation was still considered low. Local people participated in some laboring. The govemnment officials and entrepreneurs participated in implementation of the plans, 4) Joint-learning between sample groups through tourism were considered to be good. Considering the social impacts, the negative impacts of tourism on the Tarutao National Park were still small. There were some impacts on sample groups concerning garbage, deteriorating natural habitats, removing of stone and sea shells. There were problems concerning law enforcement and congestion. The problems did exist but level of the problems were still low and might be remedied through ecotourism.